2022
DOI: 10.2196/38214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After a Digital Musculoskeletal Program for Acute and Subacute Pain: Observational, Longitudinal Study With Comparison Group

Abstract: Background Telerehabilitation for musculoskeletal (MSK) conditions may produce similar or better outcomes than usual care, but most telerehabilitation studies address only chronic or postsurgical pain. Objective We aimed to examine pain and function at 3, 6, and 12 weeks for individuals with acute and subacute MSK pain who took part in a digital MSK program versus a nonparticipant comparison group. Methods W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“… 15 In a previous study, we found that participants of a digital acute MSK program showed significantly more pain and functional improvement by 12 weeks, compared to nonparticipants. 16 However, to our knowledge, there have not been any studies evaluating whether digital interventions can resolve acute pain and prevent chronic conditions from developing. Due to its multifaceted and subjective nature, pain is often a complicated and difficult outcome to measure.…”
Section: Introductionmentioning
confidence: 99%
“… 15 In a previous study, we found that participants of a digital acute MSK program showed significantly more pain and functional improvement by 12 weeks, compared to nonparticipants. 16 However, to our knowledge, there have not been any studies evaluating whether digital interventions can resolve acute pain and prevent chronic conditions from developing. Due to its multifaceted and subjective nature, pain is often a complicated and difficult outcome to measure.…”
Section: Introductionmentioning
confidence: 99%